Treatment of membranous nephropathy: Perspectives on current and future therapies - Shah, Monarch; DeLaat, Andrew; Cavanaugh, Corey (Frontiers in Nephrology, 2023)
Primary membranous nephropathy remains one of the most frequent causes of nephrotic syndrome in adults. It is an autoimmune disorder in which auto-antibodies target antigens at the podocytes cell membrane–basement membrane interface. Our understanding of membranous nephropathy has expanded dramatically as of late. After the initial discovery of the phospholipase A2 receptor auto-antibody in 2009, eight more antigens have been discovered. These discoveries have led to refinement in our understanding of the pathogenesis, diagnosis, and natural history of primary membranous nephropathy. Now, many experts advocate for redefining primary membranous nephropathy based on antigen, potentially shedding the primary and secondary nomenclature. Recently, therapies for primary membranous have also expanded. Immunosuppressive therapies like cyclophosphamide and rituximab, which primarily target B-cells, remain the cornerstone of therapy. However, there is still significant room for improvement, as many as 30-40% do not respond to this therapy according to recent trials. Additionally, drugs targeting complement, and other novel therapies are also under investigation. In this review we will discuss the available therapies for primary membranous nephropathy in light of recent clinic trials like GEMRITUX, MENTOR, RI-CYCLO, and STARMEN, as well as management strategies. While the last 10 years have seen a boom in our mechanistic understanding of this ever-diversifying disease, we are likely to see a similar boom in the therapeutic options in the years to come.